Les jeunes et la mémoire collective dans la petite ville : enjeux et conséquences - Jean-Luc Roques (Temporalités)
A small town has a low population density, and possesses a specific territorial dynamics, shaped around a selective collective memory. Questioning the life experience of those concerned, particularity the young, one finds that this collective memory is not devoid of problems. Not only does it generate a particular attitude of withdrawal, but it also feeds a distinction between « people from here » and « people from elsewhere », « us » vs. « them ». Maintaining a highly selective collective memory builds an insider identity, keeping the outside at a distance, or throwing distance out.